A historical study of the polity of the gay and lesbian ordination and/or installation, and same-gender marriage debates in the Presbyterian Church (U.S.A.) and its predecessor churches - Duncan, Graham A (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.